Evaluation of cardiovascular risk in patients with Parkinson disease under levodopa treatment - Günaydın, Zeki Yüksel; Özer, Fahriye Feriha; Karagöz, Ahmet; Bektaş, Osman; Karataş, Mehmet Baran; Vural, Aslı; Bayramoğlu, Adil; Çelik, Abdullah; Yaman, Mehmet (Journal of geriatric cardiology : JGC, 2016)
BackgroundLevodopa is the indispensable choice of medial therapy in patients with Parkinson disease （PD）. Since L-dopa treatment was shown to increase serum homocysteine levels, a well-known risk factor for cardiovascular disorders, the patients with PD under L-dopa treatment will be at increased risk for future cardiovascular events. The objective of this study is to evaluate cardiovascular risk in patients with PD under levodopa treatment.MethodsThe study population consisted of 65 patients with idiopathic PD under L-dopa treatment. The control group included 32 age and gender matched individuals who had no cognitive decline. Echocardiographic measurements, serum homocysteine levels and elastic parameters of the aorta were compared between the patients with PD and controls.ResultsAs an expected feature of L-dopa therapy, the Parkinson group had significantly higher homocystein levels （15.1 ± 3.9 μmol/Lvs. 11.5 ± 3.2 μmol/L,P = 0.02）. Aortic distensibility was significantly lower in the patients with PD when compared to controls （4.8 ± 1.5 dyn/cm2vs. 6.2 ± 1.9 dyn/cm2,P = 0.016）. Additionally, the patients with PD had higher aortic strain and aortic stiffness index （13.4% ± 6.4%vs. 7.4% ± 3.6%,P 〈 0.001 and 7.3 ± 1.5vs. 4.9 ± 1.9,P〈 0.001 respectively）. Furthermore, serum homocysteine levels were found to be positively correlated with aortic stiffness index and there was a negative correlation between aortic distensibility and levels of serum homocysteine （r = 0.674,P 〈 0.001;r=-0.602,P 〈 0.001, respectively）.ConclusionsThe patients with PD under L-dopa treatment have increased aortic stiffness and impaired diastolic function compared to healthy individuals. Elevated serum homocysteine levels may be a possible pathophysiological me-chanism.